A minor role of asparaginase in predisposing to cerebral venous thromboses in adult acute lymphoblastic leukemia patients. (15th May 2017) - Roininen, Saara; Laine, Outi; Kauppila, Marjut; Vesanen, Marko; Rämet, Maria; Sinisalo, Marjatta; Jantunen, Esa; Säily, Marjaana; Räty, Riikka; Elonen, Erkki; Wartiovaara‐Kautto, Ulla
Abstract: Cerebral venous thrombosis (CVT) covers up to a third of all venous thromboses (VTs) detected in patients with acute lymphoblastic leukemia (ALL). It usually hampers patients' lives and may also endanger efficient leukemia treatment. Although many factors have been suggested to account for an elevated risk of VTs in patients with ALL, there still is a lack of studies focusing on CVTs and especially in the setting of adult ALL patients. We studied in our retrospective population‐based cohort the occurrence, characteristics, as well as risk factors for VTs in 186 consecutively diagnosed Finnish adult ALL patients treated with a national pediatric‐inspired treatment protocol ALL2000. In the risk factor analyses for VTs we found a distinction of the characteristics of the patients acquiring CVT from those with other kinds of VTs or without thrombosis. In contrast to previous studies we were also able to compare the effects of asparaginase in relation to CVT occurrence. Notably, more than half of the CVTs were diagnosed prior the administration of asparaginase which accentuates the role of other risk factors on the pathophysiology of CVT compared to truncal or central venous line (CVL) VTs in adult ALL patients. Abstract : Asparaginase has been thought to associate with cerebral venous thromboses (CVTs) in adult patients with acute lymphoblastic leukemia (ALL). We studied the potential risk factors for CVTs in adult ALL patients and found a distinction of risk characteristics in patients acquiring CVT compared with other kinds of venous thrombosis or no thrombosis. Furthermore, we could not detect an association of asparaginase with CVTs occurrence and suggest that the ALL disease itself would endanger patients more for CVTs.